Struktur Anatomi Batang Tiga Jenis Rotan Genus Calamus dari Kawasan Tembawang Kabupaten Kubu Raya - Riza Linda, Fera Handayani, Mukarlina (Jurnal Protobiont, 2014)
Rattan?s stem, is used to make furniture and ropes. The strenght of rattan is stem classified according to vessel arrangement an dimensional fibre. The purpose of the research was to investigate anatomical structure of three types of rattan stem, namely worm rattan (Calamus asperimus Bl), sega rattan (Calamus caesius Bl), and semambu rattan (Calamus scipionum L). The research was conducted by using embedding and maceration method. According to transversal from these three types of rattan showed peripheral and central corpus area. Cortex belongs to type A that is jigsaw puzzle like with characteristics large cells, irregular inform with numerous large intercellular spaces. Vascular tissue has colateral type which consists of xylem and floem surrounded by fibers. Protoxylem of C. asperimus and C. caesius contain 1-6 cells and C. scipionum has 2-10 cells with loose arrangement. Metaxylem has round shape and has one composition in the centre of vessel. The mean of metaxylem diameter from each species (C. asperimus, C. caesius and C. scipionum) was 130,4 m, 194,0 m and 300,5 m respectively. Floem consists of two areas which contain 3-4 cells and has sequential structure. Dimensional fibre has various value depend on early cell development, stem position and age stem